DEN OPLØSTE SAMLING OG DEN MAGISKE MATERIE - Sjørslev, Inger (Tidsskriftet Antropologi, 2001)
collecting objects related to magic rituals in Brazil for the Department of Ethnography of the Danish National Museum, the article deals with the different conditions in which objects are found, and how they are embedded in their social context as well as in the context of the museum collection. The metaphors of wet and dry are used to characterize the – paradoxical – social killing – or “drying” –of the objects, when they enter the museum and are made permanent, and in principle, eternal through conservation. In Denmark, moreover, the de-accession of museum objects is virtually non existent, aside from the cases in which cultural property is repatriated. “Wet” objects are objects in social circulation. Likewise objects can be said to be wet when they are used in magic rituals, and where it is their role and fate to be destroyed and dissolved as, for instance, in order to cleanse the person for whom the ritual is performed. “Dry” objects are the permanent, de-socialised museum pieces, for which dissolution is prevented through the institution of conservation. The article includes some reflections on Marcel Mauss’ concept of hau as attached to exchange objects. Finally, the article questions whether museum objects, as objects within a global system of exchange, possess anything that bears relation to related to Mauss’ hau.